2011
DOI: 10.3402/fnr.v55i0.7122
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and lifestyle habits amongst adolescents in Bahrain

Abstract: BackgroundChanges in dietary habits and lifestyle are considered the main factors associated with several diet-related diseases in the Arab Gulf countries. The aim of this study was, therefore, to describe the dietary and lifestyle habits amongst adolescents in Bahrain.DesignA cross-sectional study was carried out amongst male and female secondary school students selected using the multi-stage stratified random sampling technique. A sample size of 735 subjects (339 males and 396 females), aged 15–18 years, was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
73
5
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 29 publications
8
73
5
1
Order By: Relevance
“…Our findings on the consumption of fruits by adolescents are in fair agreement with other researchers 47 who reported that about 25% of the Bahraini adolescents were consuming fruits daily; 32% 1-3 times a week; 15% 5-6 times a week and 27% were taking fruits rarely. However, these results showed that the fruit consumption of Pakistani's adolescents is much lower than the New Zealand, US and European adolescents.…”
Section: Discussionsupporting
confidence: 82%
“…Our findings on the consumption of fruits by adolescents are in fair agreement with other researchers 47 who reported that about 25% of the Bahraini adolescents were consuming fruits daily; 32% 1-3 times a week; 15% 5-6 times a week and 27% were taking fruits rarely. However, these results showed that the fruit consumption of Pakistani's adolescents is much lower than the New Zealand, US and European adolescents.…”
Section: Discussionsupporting
confidence: 82%
“…Other study showed that the frequency of consumed vegetable was about (81.8%) frequently 15 . This finding way high in comparison to previous studies from china (47.9%) 18 and Bahrain (26.3%) 21 . How ever one study from Malaysia found that only 19% of university students consumed vegetable more then 3 times per week 9 .…”
Section: 6% Eat Because Of Feeling Happy Discussioncontrasting
confidence: 64%
“…Evidence on Arab adolescents documents increasing consumption of fast foods and saturated fats and low consumption of fruits and vegetables in many parts of the region [20,48,50,55e59]. Although some studies find no gender differences in fast food consumption [60], others find that girls have fewer days of breakfast, more snacking, and lower consumption of milk, meat, chicken, and soda drinks than boys [48,61e64].…”
Section: Key Health Conditions and Risks Among Adolescents In Arab Comentioning
confidence: 99%